Consumer Protection in Peru: Origins, Evolution, and Main Regulatory Influences - Carranza Álvarez, César (2022)
In the following text, the authors address the origins and evolution of consumer protection in Peru, as well as highlighting the main regulatory infuences of the current 2010 Consumer Protection and Defence Code with regard to consumer sales (defective products), and the regime of abusive clauses, to which is added a reference to protection of personal data